2016
DOI: 10.3746/jkfn.2016.45.6.783
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum Extract Lowers Lymphatic Absorption of Trans Fat and Cholesterol in Rats

Abstract: Excessive intake of trans fats is a risk factor for cardiovascular diseases. Previously, we showed that green tea extract lowers intestinal absorption of cholesterol and elaidic acid in rats. This study was conducted to investigate a possible role for sorghum extract on lymphatic absorption of trans fat and cholesterol in rats. Adult male rats with lymph cannulae were infused at a rate of 3.0 mL/h for 8 h via a duodenal catheter with a lipid emulsion containing 146.4 μmol of trielaidin, 36.8 μmol of trilinoela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…TNF-α gene expression analysis revealed that K159048, K159077, K159078, K159088, K159089, K159093, and K159096 had expression levels below 0.4 (Figure 5). Inflammation is a localized response to infection and injury, arising from immune system reactions to internal and external stimuli [15]. The inflammatory response in macrophages, particularly LPS-induced inflammation, is known to be regulated by iNOS and Inflammation is a localized response to infection and injury, arising from immune system reactions to internal and external stimuli [15].…”
Section: Inflammatory Gene Expression Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…TNF-α gene expression analysis revealed that K159048, K159077, K159078, K159088, K159089, K159093, and K159096 had expression levels below 0.4 (Figure 5). Inflammation is a localized response to infection and injury, arising from immune system reactions to internal and external stimuli [15]. The inflammatory response in macrophages, particularly LPS-induced inflammation, is known to be regulated by iNOS and Inflammation is a localized response to infection and injury, arising from immune system reactions to internal and external stimuli [15].…”
Section: Inflammatory Gene Expression Analysismentioning
confidence: 99%
“…Inflammation is a localized response to infection and injury, arising from immune system reactions to internal and external stimuli [15]. The inflammatory response in macrophages, particularly LPS-induced inflammation, is known to be regulated by iNOS and Inflammation is a localized response to infection and injury, arising from immune system reactions to internal and external stimuli [15]. The inflammatory response in macrophages, particularly LPS-induced inflammation, is known to be regulated by iNOS and COX-2 enzymes [24].…”
Section: Inflammatory Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Genotypes with red and brown pericarp show elevated levels of total proanthocyanidin and total phenolic content, contributing to heightened antioxidant activities (79). Sorghum polyphenol extracts have antioxidant properties and show inhibition of the activity of cholesterol biosynthesis-related enzymes (80). Biologically active compounds linked to sorghum polyphenols have been shown to lower blood LDL (low-density lipoprotein) cholesterol levels and elevate HDL (high-density lipoprotein) cholesterol, demonstrating significant hypocholesterolemic effects.…”
Section: Phenolic Compounds In Sorghum: Diversity Distribution and He...mentioning
confidence: 99%
“…Recently, as studies on the biological functionality of sorghum grew, there were reports on its active ingredients, such as flavonoids and various phenolic components, including tannins [3]. Polyphenol extracts from sorghum exhibit antioxidant activity and inhibit the activity of enzymes related to cholesterol biosynthesis [4]. Biologically active substances related to polyphenols in sorghum suppress blood LDL (low density lipoprotein)-cholesterol and increase HDL (high density lipoprotein)-cholesterol and have excellent hypocholesterolemic effects [5].…”
Section: Introductionmentioning
confidence: 99%